Neonatal sepsis-blood culture, antibiotic stewardship and clinico-bacteriological study - Shah, Purva; Gadhvi, Ketan; Muliya, Bharat; Shah, Khushi (International Journal of Contemporary Pediatrics, 2020)
Background: Neonatal sepsis refers to an infection involving bloodstream in newborn infants less than 28 days old. It continues to remain a leading cause of morbidity and mortality among infants, especially in middle and lower-income countries. Neonatal sepsis is divided into 2 groups based on the time of presentation after birth: early-onset sepsis and late-onset sepsis. Methods: This study was done in the neonatal intensive care unit of tertiary hospital, Surendranagar. Study design being observational, data collected from clinical examination and records of the neonates admitted with positive septic screen, neonates admitted with suspected clinical sepsis (temperature >990F or <950F, respiratory rate more than 60 per minute, change in behavior, abnormal cry, not accepting feed, drowsy or unconscious, septic focus on skin or umbilicus, diarrhea and seizures) and neonates admitted with culture positive sepsis. Results: As per this research, neonatal sepsis has more male preponderance, with more commonly occurring in low birth weights and preterm. Klebsiella, Staphylococcus aureus and Pseudomonas being the most isolated organisms. Their resistance pattern, antibiotic profile and newer trends also came across. Conclusions: Neonatal sepsis comes as one of the major causes of mortality and morbidity of the newborns admitted. By this research, analyzing the sex, age, gestational weeks, organism isolated and the antibiotic profile, emerging new resistance and newer useful antibiotics can thus be studied and can be taken as a base for further study as well as evaluation of the same, along with also guiding to manage and treat neonatal sepsis better.